Neuroblastoma patient‐derived cultures are enriched for a mesenchymal gene signature and reflect individual drug response. Issue 10 (28th August 2020) - Hee, Esther; Wong, Meng Kang; Tan, Sheng Hui; Choo, Zhang'E; Kuick, Chik Hong; Ling, Sharon; Yong, Min Hwee; Jain, Sudhanshi; Lian, Derrick W. Q.; Ng, Eileen H. Q.; Yong, Yvonne F. L.; Ren, Mee Hiong; et al.
Abstract: Ex vivo evaluation of personalized models can facilitate individualized treatment selection for patients, and advance the discovery of novel therapeutic options. However, for embryonal malignancies, representative primary cultures have been difficult to establish. We developed patient‐derived cell cultures (PDCs) from chemo‐naïve and post–treatment neuroblastoma tumors in a consistent and efficient manner, and characterized their in vitro growth dynamics, histomorphology, gene expression, and functional chemo‐response. From 34 neuroblastoma tumors, 22 engrafted in vitro to generate 31 individual PDC lines, with higher engraftment seen with metastatic tumors. PDCs displayed characteristic immunohistochemical staining patterns of PHOX2B, TH, and GD2 synthase. Concordance of MYCN amplification, 1p and 11q deletion between PDCs and patient tumors was 83.3%, 72.7%, and 80.0% respectively. PDCs displayed a predominantly mesenchymal‐type gene expression signature and showed upregulation of pro‐angiogenic factors that were similarly enriched in culture medium and paired patient serum samples. When tested with standard‐of‐care cytotoxics at human C max ‐equivalent concentrations, MYCN ‐amplified and non‐ MYCN ‐amplified PDCs showed a differential response to cyclophosphamide and topotecan, which mirrored the corresponding patients' responses, and correlated with gene signatures of chemosensitivity. In this translational proof‐of‐concept study, early‐phase neuroblastoma PDCs enriched for the mesenchymal cell subpopulation recapitulated the individual molecular and phenotypic profile of patient tumors, and highlighted their potential as a platform for individualized ex vivo drug‐response testing. Abstract : We developed a system to efficiently and consistently generate patient‐derived cultures (PDCs) of neuroblastoma that recapitulated individual patient's cytogenetic and immunohistochemical features, and phenotypic responses to standard‐of‐care chemotherapy. PDCs predominantly express the gene signature of the recently described neuroblastoma mesenchymal super‐enhancer state. This proof‐of concept provides translational evidence supporting the proposed role of the mesenchymal cell subpopulation in determining clinical treatment response and offers a novel platform for developing personalized ex vivo therapeutic decision‐making strategies for neuroblastoma.